JANUARY 1991. (Computer (00189162), 2007)
Several excerpts from articles about computers that was published in the January 1991 issue of this periodical are presented. Topics of the articles include massive parallelism of machines, the diversity of the architectural designs of the computers, neural networks, and the performance of microsupercomputers.